2023
DOI: 10.1002/elps.202300005
|View full text |Cite
|
Sign up to set email alerts
|

Combined electroosmotic and pressure‐driven transport of neutral solutes across a rough, porous‐walled microtube

Abstract: A number of microfluidic systems of interest essentially consist of micro‐scaled channels/tubes, whose walls are inherently rough. The novelty of the current study lies in exploring the impact of the wall roughness on mass transfer in the case of flow through a microtube with porous wall. The current investigation is possibly the first attempt at exploring the effect of mass transfer for a porous‐walled, rough microtube, as earlier studies were limited to the analysis of hydrodynamic and thermal effects only i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Roy et al [14] carried out a theoretical study on the transport of a neutral solute in incompressible electro-osmotic flow of Bingham plastic non-Newtonian liquid flowing through a microchannel. Sengupta et al [15] reported a study on the combined transport of electroosmosis and pressure-driven flow in rough porous-walled microtubules.…”
Section: Introductionmentioning
confidence: 99%
“…Roy et al [14] carried out a theoretical study on the transport of a neutral solute in incompressible electro-osmotic flow of Bingham plastic non-Newtonian liquid flowing through a microchannel. Sengupta et al [15] reported a study on the combined transport of electroosmosis and pressure-driven flow in rough porous-walled microtubules.…”
Section: Introductionmentioning
confidence: 99%